The technical principles of bilingual lexicography (In the context of Urdu and Pashto bilingual lexicography) - Sher, Ali; Munir Bukhari, Badshah (sourcecoder, 2022)
This article, as the premier work introducing the principles of bilingual lexicography from a technical perspective, is launched to represent original thinking and innovative theorization in the field of bilingual lexicography. It treats the bilingual dictionary as a system of intercultural communication and bilingual dictionary making as a dynamic process realized by sets of choices, characterizing the overall nature of the dictionary. It examines the dictionary and dictionary making by using a model of lexicography which stresses the three-way relationship of compiler, dictionary context and user and incorporates them into a unified coherent framework. Throughout the study, special focus is on Urdu and Pashto bilingual lexicography. In the article not only discuss all the main practical and theoretical issues in lexicography for Urdu and Pashto , but a thorough treatment of the processes involved within a communicative model, as the bilingual dictionary is seen as what it can be at its best: an indispensable learning tool. A bilingual dictionary, like other dictionaries, is an imperfect method of describing the lexicon in one or two languages, yet, given the nature of dictionary consultation, it can be successfully used in prediction, i.e. in production of linguistic forms or meanings which serve in the process of communication’